ANALISIS EFISIENSI PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY DAN METODE ECONOMIC PRODUCTION QUANTITY PADA ROTI GANEP SOLO - Maesprillanti Maesprillanti; Yohanes Djoko Suseno; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
Roti Ganep Solo is a company engaged in the food industry, especially bread whose main raw materials are glutinous rice flour, wheat flour, and arrowroot flour, because companies still use conventional methods in controlling raw material inventory, by introducing the method of economic order quantity and the method of economic production quantity are expected to be used to optimize the supply of raw materials by the company. EOQ a method by which a company purchases raw materials with the quantity of goods obtained as well as minimal cost, while EPQ is a method used to consider between the amount of production and the amount of demand for production. Based on this application of the EOQ method and the EPQ method can play a role ini streamlining the control of raw material inventory at Roti Ganep Solo. Hal tersebut ditunjukan dengan total biaya persediaan bahan baku menggunakan metode EOQ Rp 4.988.477 with an average purchase of 1.726 kg with 14 orders, while using the conventional method the company has a total inventory cost of Rp 5.062.488 with the purchase of 2.500 of raw material per month, for the use of the EPQ method produce a total annual cost of Rp 17.209.464 for an average purchase of 44.870 pcs, whereas using the conventional method the company produces an average raw material of 56.484 pcs.